Evaluación del proceso de infección por Lecanicillium fungicola en Agaricus bisporus por microscopia electrónica de barrido - Santana Nunes, Janaira; Rocha de Brito, Manuela; Cunha Zied, Diego [UNESP]; Aparecida das Graças Leite, Eloisa; Souza Dias, Eustáquio; Alves, Eduardo (Elsevier, 2017)
Background Lecanicillium fungicola causes dry bubble disease in Agaricus bisporus mushrooms leading to significant economic losses in commercial production. Aims To monitor the infection process of L. fungicola in Brazilian strains of A. bisporus. Methods The interaction between the mycelium of L. fungicola (LF.1) and three strains of A. bisporus (ABI 7, ABI 11/14 and ABI 11/21) was studied. Electron microscopy and X-ray microanalyses of vegetative growth and basidiocarp infection were evaluated. Results Micrographs show that the vegetative mycelium of the Brazilian strains of A. bisporus is not infected by the parasite. The images show that the pathogen can interlace the hyphae of A. bisporus without causing damage, which contributes to the presence of L. fungicola during the substrate colonization, allowing their presence during primordial formation of A. bisporus. In the basidiocarp, germ tubes form within 16 h of infection with L. fungicola and the beginning of penetration takes place within 18 h, both without the formation of specialized structures. Conclusions Scanning electron microscopy enabled the process of colonization and reproduction to be observed within the formation of phialides, conidiophores and verticils of L. fungicola. The formation of calcium oxalate crystals by the pathogen was also visible using the X-ray microanalysis, both at the hyphae in the Petri plate and at basidiocarp infection site.
Evaluation of the infection process by Lecanicillium fungicola in Agaricus bisporus by scanning electron microscopy
Keywords: Mushroom; Mycopathogen; Scanning electron microscopy; X-ray microanalyses